Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology. (August 2023) - Cui, Xin-Ru; Wang, Yu-Sheng; Chen, Yan; Mu, Hong-Yan; Chen, Hai-Hua
Abstract: In this study, WS-CA complexes were prepared with wheat starch (WS) and caffeic acid (CA) by the hot-extrusion 3D printing (HE-3DP) technology. In vitro digestion experiment was performed to investigate the effects of CA on WS digestibility. Moreover, the effects of CA on WS structures as well as amylase activities (both α-amylase and α-glucosidase) were studied by X-ray diffraction, multi-spectroscopy, and molecular simulation methods. The results of in vitro digestion showed that digestibility of WS-CA complexes decreased significantly compared to that of WS. FT-IR spectroscopy and X-ray diffraction demonstrated that CA and WS formed a highly ordered B + V-type crystalline structure by hydrogen bonding. According to the enzyme inhibition kinetic results, CA was able to inhibit α-amylase (PPA) and α-glucosidase (SCG) activities in a competitive-type manner and mixed-type manner, respectively. Molecular modelling results showed that CA mainly bound to Asp197 at the active sites of PPA and Asp233 at the hydrophobic cavity of SCG, which could increase amylase's structural rigidity and prevent WS from contacting enzymes. The results of logarithm-of-slope model suggested that CA could change WS structures, inhibit amylase activities and reduce WS digestibility under the synergistic effects. These findings could offer valuable information on CA reducing starch digestibility by the HE-3DP technology. Graphical abstract: Image 1 Highlights: WS-CA complex prepared by hot-extrusion 3D printing reduced WS digestion. B + V-type crystalline was formed between WS and CA through non-covalent interactions. CA bound to the residues in the active sites of PPA and the hydrophobic cavity of SCG. CA inhibited PPA and SCG activities through competitive inhibition and mixed inhibition. WS digestion decreased by changing WS structure and inhibiting amylase activities.